2017
DOI: 10.1111/1467-8268.12232
|View full text |Cite
|
Sign up to set email alerts
|

Oil and Regional Development in Chad: Assessment of the Impact of the Doba Oil Project on Poverty in the Host Region

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Resource extraction projects are typically associated with a large influx of job-seeking migrants into the resource area (IFC, 2009;Aristide and Moundigbaye, 2017). Such population growth frequently leads to new types of poverty and other social problems, such as alcohol abuse and prostitution (Vanclay, 2002;Pegg, 2006;Vanclay et al, 2015;Hansen et al, 2016;Esteves et al, 2017).…”
Section: The Impacts Of Oil Development Activities On Local Livelihoodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Resource extraction projects are typically associated with a large influx of job-seeking migrants into the resource area (IFC, 2009;Aristide and Moundigbaye, 2017). Such population growth frequently leads to new types of poverty and other social problems, such as alcohol abuse and prostitution (Vanclay, 2002;Pegg, 2006;Vanclay et al, 2015;Hansen et al, 2016;Esteves et al, 2017).…”
Section: The Impacts Of Oil Development Activities On Local Livelihoodsmentioning
confidence: 99%
“…Oil discoveries in other African countries have created a mixture of optimism and pessimismwith the discovery of oil in Chad, for example, being heralded by its leaders and development partners in the 1990s "as a unique opportunity to generate resources to spend on poverty reduction activities" (Aristide and Moundigbaye, 2017:42). However, as time went by, few tangible benefits for local peoples in Chad have actually emerged (Aristide and Moundigbaye, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the discovery of oil has also come with negative consequences for local people, including rent seeking, social conflict, and a local resource curse, which is similar to the experiences of other oil-producing countries [3,7,[9][10][11][12]. Many scholars have identified that oil tends to be associated with resource curse issues, including corruption, instability, and economic underperformance [13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%